Analisis Empiris Dampak Pernikahan Dini terhadap Kemiskinan dan Kesejahteraan Keluarga: Studi Berdasarkan Indikator Keluarga Sakinah Kementerian Agama dalam Perspektif Hukum Keluarga Islam di Desa Maroon - m supri; Ana Billah (Jurnal Hukum Lex Generalis, 2026)
The practice of early marriage in Maroon Village has become a social issue linked to poverty, low levels of education, and poor family well-being. Although the minimum age for marriage is stipulated in Law No. 16 of 2019, research on the impact of early marriage on family well-being—based on the Ministry of Religious Affairs’ “sakinah” family indicators—remains limited. This study aims to analyze the relationship between early marriage, poverty, and family wellbeing from the perspective of Islamic family law using a socio-legal approach. Data were collected through interviews and observations, then analyzed descriptively using the “sakinah family” indicators and the maqāṣid al-syarī‘ah. The results show that early marriage is influenced by economic, educational, and cultural factors, as well as premarital pregnancy, and leads to low family wellbeing. This study contributes by integrating the Ministry of Religious Affairs’ “sakinah family” indicators and maqāṣid al-syarī‘ah as instruments for empirical analysis in the study of Islamic family law.